Shallow Acupuncture for Chronic Neck Pain: A Multicenter Randomized Controlled Trial Protocol with fMRI and DTI - Lin J; Gu Z; Zhou P; Huang W; Ou A; Zhao Q; Xu Z (Journal of Pain Research)
Jiahui Lin,1 Zhilin Gu,1 Peng Zhou,2 Weikang Huang,1 Aihua Ou,1 Qi Zhao,3 Zhenhua Xu1 1The second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 2Department of Acupuncture, Shenzhen Bao’an Traditional Chinese Medicine Hospital, Shenzhen, People’s Republic of China; 3National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of ChinaCorrespondence: Qi Zhao, National Clinical Research Center for Chinese Medicine Acupuncture and Moxibustion, First Teaching Hospital of Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China, Email houhaowen2@163.com Zhenhua Xu, The second Clinical College of Guangzhou University of Chinese Medicine, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China, Email xzh197011@163.comPurpose: This study aims to explore the central mechanisms of shallow acupuncture for chronic neck pain (CNP) using functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI), an innovative approach not commonly applied in shallow acupuncture research.Patients and Methods: This multi-center randomized controlled trial will recruit 252 CNP patients from three centers (84 per center). Participants will be randomly assigned to three groups: shallow acupuncture, drug control (celecoxib capsules), or waiting list group, with 84 patients per group. The primary outcomes include total effective rate, visual analogue scale (VAS), Neck Disability Index (NDI), and brain imaging results (20 randomly selected patients per group). Secondary outcomes include the Self-Rating Anxiety Scale (SAS), Short Form 36 Questionnaire (SF-36), and cervical range of motion (CROM). Data will be collected at baseline, after 2 weeks, and at 3-month follow-up. fMRI and DTI data will be collected at baseline and after 2 weeks. Analyses will include regional homogeneity (ReHo), amplitude of low-frequency fluctuations (ALFF), functional connectivity (FC), fractional anisotropy (FA), and mean diffusivity (MD) within and between groups. An additional 20 healthy volunteers will provide baseline fMRI and DTI data for comparison.Conclusion: This study will validate the clinical efficacy of shallow acupuncture for CNP and explore its central mechanisms using fMRI and DTI. The findings may provide neuroimaging evidence supporting the broader clinical application of shallow acupuncture in treating CNS-related diseases.Keywords: chronic neck pain, shallow acupuncture, brain functional networks, clinical trial protocol